ANALISA PELAYANAN ADMINISTRASI UNIVERSITAS PROF. DR. HAZAIRIN, SH BENGKULU - Idham Lakoni (Universitas Prof. Dr. Hazairin SH, 2018)
Creating services that need continuous customer needs and needs that change and cannot be predicted from time to time. Therefore the company opens to accept the types of input, criticism and complaints from consumers, then helps, finds solutions and makes improvements. Future service marketing certainly provides investors with opportunities to develop ever-increasing businesses that support development that uses information and technology used. Specific research is qualitative descriptive through primary data through questionnaires and samples of students in Unihazual semesters IV and VI with purposive sampling technique. Research results show that there is no service consisting of variables such as reliability, responsiveness, competence, credibility, physical evidence, assurance and empathy, which are still a concern to continue to be improved so that in the future unihaz services will be better